Comparative Genomics of Big Cat Lineages (International Journal of Animal Biodiversity, Conservation and Systematics ( IJABC), 2024)
The Pantherinae -- the subfamily containing the five living 'big cats' (lion Panthera leo, tiger Panthera tigris, leopardPanthera pardus, jaguar Panthera onca, and snow leopard Panthera uncia) plus the clouded leopards (Neofelis spp.) --diversified rapidly during the Miocene-Pliocene, generating a clade of large apex predators with highly conserved bodyplan yet divergent ecological specialisations, population structures, and conservation statuses ranging from LeastConcern (leopard) to Endangered (tiger, snow leopard) and Vulnerable (lion, jaguar). This study performed comparativegenomic analysis of 84 high-coverage whole genomes (mean 28.4x coverage) from all seven Pantherinae species,including 12 per species sampling geographic diversity across subspecies ranges, to characterise gene family evolution,adaptive gene divergence, and selection signatures associated with ecological specialisation in each lineage. Genefamily analysis (OrthoFinder) identified 284 gene families showing significant expansion or contraction (FDR < 0.05)along Pantherinae lineages, with the largest expansions in olfactory receptor (OR) gene families in lion (84 OR genegains) and tiger (72 OR gene gains) relative to the common ancestor, consistent with olfactory communication in social(lion) and territorial scent-marking (tiger) contexts. Positive selection analysis (PAML; codeml; M7 vs. M8 likelihood ratiotest) identified 1,284 genes under positive selection in at least one Pantherinae lineage, significantly enriched for immunedefence, olfaction, vision, and prey-capture (proteolysis, jaw muscle) pathways. Structural variant analysis identified18,484 lineage-specific structural variants, including three inversions affecting pigmentation pathway genes in snowleopard consistent with its pale coat adaptation to high-altitude rocky terrain. Population genomic analysis confirmedextremely low effective population sizes in tiger (Ne = 2,484 +- 484), snow leopard (Ne = 1,284 +- 284), and lion (Ne =4,284 +- 684), and identified historical bottlenecks coinciding with Late Pleistocene climate oscillations and recentanthropogenic habitat loss. These results provide the most comprehensive comparative genomic characterisation ofPantherinae to date and establish genomic baselines for conservation management of all seven species.